Is Bullying a Moral Disability? Identification of Bullying Behavior In Kindergarten - Uswatun Nisa (Institut Agama Islam Negeri Madura, 2024)
The phenomenon of bullying is a crucial issue that invoked children’s daily lives in school environment. Bullying does not only occured at primary and secondary school levels, but generally its existence can be identified since children on the early educational stage. Understanding bullying behavior and actions carried out by children, both as actors and victims, required serious treatment. Children are in the early cognitive development phase and have a moral dilemma, which causes bullying to become a nature. This research is a qualitative study with a phenomenological approach to explore narratives of bullying behavior on early childhood in kindergarten schools spread across the Kalimantan region. Through obtaining informant data from teachers at schools, it was found that bullying usually happen in physical, verbal and relational forms. Gender differences between boys and girls also influence the tendency for forms of bullying. Teachers' mechanism efforts to overcome bullying are brought in many strategies that focus on both the perpetrator, target and mediator.